Molecular investigation of MEFV gene polymorphisms among patients with familial mediterranean fever-like symptoms: MEFV genetic testing and FMF diagnosis - Ahmed , Nashwa E.; El Gazzar, Walaa Bayoumie; Amer, Arwa S.; Elamawy, Medhat; Eleleimy, Hiam Abdallah; El-Shimi, Ola; Elmahdy, Mai; El-Sayed, Marwa Said; Abdelrahman, Shaymaa M. (Cellular and Molecular Biology, 2024)
The diagnosis of familial Mediterranean fever (FMF) is primarily based on clinical standards. The purpose of this study was to investigate the relevance of Mediterranean fever (MEFV) genetic testing in the diagnosis of FMF as well as to identify the most frequent variant alleles and their relationship to clinical symptoms in Egyptian patients. Egyptian patients with a clinical suspicion of having FMF were studied in order to determine MEFV genotypes. Each patient was meticulously evaluated through an extensive collection of their medical history, a thorough clinical examination, and a series of laboratory tests, encompassing CBC, ESR, and CRP measurements. The MEFV variant screening procedure included the use of reverse dot blot hybridization. The average age of our patients when they were given a diagnosis was 22.8 ± 1.404 years old. The predominant clinical manifestations identified were abdominal pain, fever, and arthralgia. Molecular interrogation of the MEFV gene unveiled that a significant proportion of the cohort, constituting 72 individuals (60%), displayed heterozygosity, whereas a smaller fraction, comprising 12 subjects (10%), demonstrated homozygosity and an equivalent number (10%) exhibited compound heterozygosity. Pertaining to the distribution of allele variants, E148Q emerged as the most prevalent, succeeded by M694I, accounting for 12.5% of the cases, and M680I (G/A), representing 10.41%. This notable prevalence of heterozygous genotypes among the Egyptian demographic, preliminarily identified as potential FMF cases, underscores the imperative for molecular diagnostics to enhance the precision of FMF identification.